Implikasi Citra Kandidat Terhadap Perilaku Golput (Turnout) di Moderatori Oleh Kepercayaan Pada Pemilih Muda Kota Samarinda - Syahrin, M Najeri Al; Astuti, Tri (Universitas Muhammadiyah Sorong, 2023)
The characteristics of young voters are critical, independent, independent, anti-status quo, and pro-change as a new force in democracy, but many do not use their voting rights properly. An important factor why young voters do not choose candidates in elections (abstention) is due to aspects of the candidate's trust and image that do not meet the qualifications and expectations. This research seeks to determine the role of candidate image in elections which can influence the abstention behavior (turnout) of young voters with trust as the main moderator variable. The approach used in this research is quantitative with a research sample of 135 young voters in Samarinda. Data analysis uses multiple regression analysis using the Statistical Product and Service Solutions (SPSS) program. This research obtained results after a regression analysis was carried out from the results of multiplying the candidate's image and trust which was marked with the product symbol. The result is that the product is not able to predict abstention behavior well. It can be concluded that the candidate's image and trust can predict high abstention behavior. However, trust was not proven to be a moderator of the relationship between candidate image and abstention behavior. Trust cannot be a moderator variable for certain reasons, namely because trust can be independent of the influence of the candidate's image. Subjects were more likely to differentiate between candidate image and trustworthiness and the two were not connected.